DICCIONARIO BIOGRÁFICO DE LA CATEDRAL DE CÓRDOBA (I): LOS MIEMBROS DEL CABILDO EN ÉPOCA MODERNA - Díaz Rodríguez, Antonio J. (2016)
This paper presents the first part of the biographical study of a representative number of the members of a Spanish cathedral chapter, that of Cordoba, between the last fifteenth century and the first years of the nineteenth century. To do that, I chose a format of simplified entries with basic information on the origin, parentage, studies and career of several hundred churchmen.